The project manager's guide to mastering agile : principles and practices for an adaptive approach - Cobb, Charles G., 1945- (John Wiley & Sons, Inc., 2023)
"Agile project management is an iterative approach to delivering a project throughout its life cycle. Agile life cycles are composed of several iterations or incremental steps towards the completion of a project. Iterative approaches are frequently used in software development projects to promote velocity and adaptability since the benefit of iteration is that you can adjust as you go along rather than following a linear path. One of the aims or an agile or iterative approach is to release benefits throughout the process rather than only at the end. Agile projects should exhibit values and behaviors of trust, flexibility, empowerment, and collaboration"--